The “Jack-of-all-Trades” Flagellum From Salmonella and E. coli Was Horizontally Acquired From an Ancestral β-Proteobacterium - Ferreira, Josie L.; Coleman, Izaak; Addison, Max L.; Zachs, Tobias; Quigley, Bonnie L.; Wuichet, Kristin; Beeby, Morgan (Frontiers in Microbiology, 2021)
The γ-proteobacteria are a group of diverse bacteria including pathogenic Escherichia, Salmonella, Vibrio, and Pseudomonas species. The majority swim in liquids with polar, sodium-driven flagella and swarm on surfaces with lateral, non-chemotactic flagella. Notable exceptions are the enteric Enterobacteriaceae such as Salmonella and E. coli. Many of the well-studied Enterobacteriaceae are gut bacteria that both swim and swarm with the same proton-driven peritrichous flagella. How different flagella evolved in closely related lineages, however, has remained unclear. Here, we describe our phylogenetic finding that Enterobacteriaceae flagella are not native polar or lateral γ-proteobacterial flagella but were horizontally acquired from an ancestral β-proteobacterium. Using electron cryo-tomography and subtomogram averaging, we confirmed that Enterobacteriaceae flagellar motors resemble contemporary β-proteobacterial motors and are distinct to the polar and lateral motors of other γ-proteobacteria. Structural comparisons support a model in which γ-proteobacterial motors have specialized, suggesting that acquisition of a β-proteobacterial flagellum may have been beneficial as a general-purpose motor suitable for adjusting to diverse conditions. This acquisition may have played a role in the development of the enteric lifestyle.